(untitled) (Biological Sciences - PJSIR, 2022)
Four cotton cultivars viz. Qalandari, MNH-93, Rchrnani and S-12 were analysed for their leaf chlorophyll fluorescence properties, at normal growth temperature (30°) (control), and shocked at high temperature (45°) for different time periods. There were only small variations in the values of chlorophyll fluorescence at the control temperature. However, the photosystem of the leaves was irreversibly damaged as assessed by fluorescence properties when the leaves were shocked at 45° for 30 mins or longer. All the cultivars were equally sensitive to the treatment.